POTENSI PERTUMBUHAN PENDUDUK DAN EKONOMI DALAM PENGEMBANGAN WILAYAH KELURAHAN TANJUNG PINGGIR KECAMATAN SEKUPANG - Farid Ahmad Marzuki; Rahmad Hidayat; Yuanita FD Sidabutar (Universitas Batam, 2023)
One of the development indicators for the development of a region is the increase in population growth and the community's economy. Tanjung Pinggir Village is one of the areas in the Sekupang District where the development of the area is less vibrant when compared to other areas in the Sekupang District. Regional development activities can be carried out by studying the potential aspects of the population and economic aspects of the region. This study aims to discuss the population and economic growth sector in the development of the Tanjung Pinggir Village area, then map its potential and opportunities and provide recommendations for regional development based on a descriptive and SWOT approach. The data used are secondary data and primary data. The results of the SWOT analysis were obtained through secondary and primary data processing with an orientation toward optimizing the utilization of the functions of residential/residential areas and the functions of trade and service areas in supporting the development of the Tanjung Pinggir Village area, Sekupang District.